Repeated therapeutic lumbar punctures in cryptococcal meningitis – necessity and/or opportunity?. Issue 6 (December 2016) - Chang, Christina C.; Perfect, John R.
Abstract : Purpose of review: Overall, 50–70% of patients with cryptococcal meningitis have raised intracranial pressure (ICP). Multiple international treatment guidelines recommend repeated therapeutic lumbar punctures as adjunctive management. Here, we review the recent evidence for the role of repeated lumbar punctures on clinical outcome in cryptococcal meningitis and also review the increasing body of data utilizing these repeated cerebrospinal fluid (CSF) samples as a window into understanding immunopathogenesis of cryptococcal meningitis. Recent findings: Adjunctive dexamethasone led to higher adverse advents and disability and poorer CSF fungal clearance. Performance of a therapeutic lumbar puncture is associated with 69% relative survival protection. An activated innate immune system in the CSF is associated with future cryptococcosis-associated immune reconstitution inflammatory syndrome development. The zebrafish model is being utilized in cryptococcal studies allowing live visualization of central nervous system invasion. Summary: Therapeutic lumbar punctures are a critical part of cryptococcal meningitis management and CSF immunological assays are increasingly being performed in research settings. Finer manipulation of CSF removal and safer surgical techniques for intracranial pressure management applicable to resource-limited settings are needed. More precise and validated guidelines in resource-available settings would be an improvement for care. We look forward to identifying a set of biomarkers, easily performed in routine laboratories or at point-of-care, so as to translate these assays into clinical care. Wide-scale '–omic' studies are likely to be required in future cryptococcal meningitis studies to improve our understanding of this deadly fungus.